Boiling heat transfer and CHF for subcooled water flowing in a narrow channel due to power transients. Issue 1 (2nd January 2020) - Shibahara, M.; Liu, Q.S.; Hata, K.; Fukuda, K.
ABSTRACT: The transient critical heat flux (CHF) of subcooled water flowing in a narrow channel was measured. A small tube with an inner diameter of 1.0 mm was heated by a direct current. The effects of the subcooling, pressure, flow velocity, and e-folding times of the heat generation rate on the transient CHF were investigated. The experimental result showed that an initial temperature overshoot appeared as the e-folding time of the heat generation rate decreased. The CHF increased with a shorter e-folding time of the heat generation rate. Finally, an empirical correlation for the transient CHF was obtained.